1998
DOI: 10.1023/a:1006006203372
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: An alpha-glucosidase cDNA clone derived from barley aleurone tissue was expressed in Pichia pastoris and Escherichia coli. The gene was fused with the N-terminal region of the Saccharomyces cerevisiae alpha-factor secretory peptide and placed under control of the Pichia AOX1 promoter in the vector pPIC9. Enzymatically active, recombinant alpha-glucosidase was synthesized and secreted from the yeast upon induction with methanol. The enzyme hydrolyzed maltose > trehalose > nigerose > isomaltose. Maltase activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Thus, unlike the barley 6-SFT, the recombinant enzyme seems to be able to form L(2C1) as well as L(2C6) linkages. A similar change of enzyme speci¢city has been observed by Tibbot et al when expressing barley K-glucosidase in Pichia [10].…”
Section: Characterization Of Enzyme Activities Produced By P1supporting
confidence: 82%
See 1 more Smart Citation
“…Thus, unlike the barley 6-SFT, the recombinant enzyme seems to be able to form L(2C1) as well as L(2C6) linkages. A similar change of enzyme speci¢city has been observed by Tibbot et al when expressing barley K-glucosidase in Pichia [10].…”
Section: Characterization Of Enzyme Activities Produced By P1supporting
confidence: 82%
“…Here we demonstrate that barley 6‐SFT can also be functionally expressed in the methylotrophic yeast Pichia pastoris . This yeast, which has been used to produce various heterologous proteins [7–10], is particularly well suited to studying the plant sucrose‐metabolizing enzymes formed by way of the secretory pathway, since it does not itself secrete sucrose‐metabolizing enzymes such as invertase [11], and since glycosylation of secreted proteins in Pichia is expected to be closer to that in plants than that in Saccharomyces cerevisiae [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the production of rAGL, up to now, most bacterial enzymes from Sulfolobus tokodaii [49] , Thermoplasma acidophilum [50] , Pyrobaculum aerophilum [51] , and Bifidobacterium longum [52] , were overexpressed in E. coli , and several AGLs from plants and fungi like barley [48] , Rice [53] ,Aspergillus niger [54] , were successfully produced in P. pastoris . In the previous work, efforts have been made to produce the rAGL of glycoside hydrolase family GH31 from higher plants in E. coli , but resulted in no or rather low enzyme activity [55][56] . It was not until 2006 that the AGL from barley (Hordeum vulgare ) with fully activity was produced in P. pastoris for the first time [47][48] .…”
Section: Figure 6 4 Discussionmentioning
confidence: 99%
“…A transcript encoding the 103 kDa protein has been identified, but it is not known whether it is translated. Tibbot et al [ 17 ] detected proteins estimated to be of 95 and 101 kDa in endosperm of germinating seeds using an antiserum raised to recombinant Agl97. However, the predicted 103 kDa protein has no apparent signal peptide cleavage site in the first 53 amino acids (SignalP 4.1, http://www.cbs.dtu.dk/services/SignalP-4.1 ) so it is not clear whether it could give rise to mature proteins of the masses detected by Tibbot et al…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 , 23 ]). Tibbot et al [ 17 ] observed that the principal proteins in endosperm recognised by an Agl97 antiserum were of 101 and 95 kDa at 4 dpi, but of only 81 kDa two days later. Other possible modifications include variable levels of glycosylation and non-enzymic glycation, both of which have been proposed to account for the occurrence of multiple forms of other endosperm proteins [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%